Developing capabilities to engage start-ups in the context of public procurement of innovation: a template analysis. Issue 4 (2nd October 2022) - Talebi, Alireza; Rezania, Davar; Bragues, George
ABSTRACT: Public institutions need to find solutions to various civic issues by stimulating the links between start-ups, innovation, and co-creation. They often turn to project management as a method of integrating various functional areas for planning and managing innovation. While the organisation and management literature recognise that identifying and managing stakeholders provides valuable resources necessary for the success of projects, little attention has been given to which capabilities are required to engage start-ups. Similarly neglected in the literature has been the development process of these capabilities. We propose that the context of sustainability-oriented innovation provides a theoretical foundation for identifying capabilities needed for engaging start-ups in a public procurement of innovation programme. We conduct a case study of a public procurement of innovation during a two-year period to examine capabilities: networking, competence mapping, relational, and desorptive. Utilising template analysis, the results indicate refinements to networking and competence mapping capabilities. The results provide a model explaining how projects in the innovation programme develop capabilities along the phases of initiation, execution, and closing. The findings suggest what public organisations can do to engage start-ups in their procurement for innovation process.